The boy who followed his father into Auschwitz : a true story of family and survival - Dronfield, Jeremy (New York : Harper, 2020)
In 1939, Gustav Kleinmann, a Jewish upholsterer in Vienna, was seized by the Nazis. Along with his teenage son Fritz, he was sent to Buchenwald in Germany. There began an unimaginable ordeal that saw the pair beaten, starved, and forced to build the very concentration camp they were held in. When Gustav was set to be transferred to Auschwitz--a certain death sentence--Fritz refused to leave his side. Throughout the horrors they witnessed and the suffering they endured, there was one constant that kept them alive: the love between father and son.
Part I, Vienna -- 1. "When Jewish blood drips from the knife..." -- 2. Traitors to the people -- Part II, Buchenwald -- 3. Blood and stone: Konzentrationslager Buchenwald -- 4. The stone crusher -- 5. The road to life -- 6. A favorable decision -- 7. The new world -- 8. Unworthy of life -- 9. A thousand kisses -- 10. A journey to death -- Part III, Auschwitz -- 11. A town called Oświecim -- 12. Auschwitz-Monowitz -- 13. The end of Gustav Kleinmann, Jew -- 14. Resistance and collaboration: the death of Fritz Kleinmann -- 15. The kindness of strangers -- 16. Far from home -- 17. Resistance and betrayal -- Part IV, Survival -- 18. Death train -- 19. Mauthausen -- 20. The end of days -- 21. The long way home --- Epilogue: Jewish blood.
Includes P.S. insights, interviews, and more.
Includes bibliographical references and index.
Keywords: Kleinmann, Gustav, -- 1891-1976.; Kleinmann, Fritz, -- 1923-; Buchenwald (Concentration camp); Auschwitz (Concentration camp); Fathers and sons -- Austria -- Vienna -- Biography; Holocaust, Jewish (1939-1945) -- Austria -- Vienna -- Personal narratives; Personal narratives